MOTOR PERFORMANCE OF PREMATURE INFANTS DISCHARGED FROM THE NEONATAL INTENSIVE CARE UNIT AND ITS ASSOCIATION WITH TIME AFTER HOSPITAL DISCHARGE (Movimenta (ISSN 1984-4298), 2023)
Objective: to analyze the motor performance of premature infants discharged from the Neonatal Intensive Care Unit (NICU) immediately after hospital discharge and verify associations with neonatal data (gestational age, birth weight, Apgar score), length of hospital stay, time after hospital discharge and corrected age on the day of assessment. Method: Cross-sectional observational study that included premature infants (GA
Keywords: Premature Infant; Neonatal Intensive Care Unit; Motor Performance